Moving color : early film, mass culture, modernism - Yumibe, Joshua (New Brunswick, N.J. : Rutgers University Press, 2012)
Moving Color is the first book-length study of the beginnings of color cinema. It traces the legacy of color history from the beginning of the nineteenth century to the cinema of the early twentieth century and explores the implications of this genealogy on experimental and contemporary digital cinemas.
Foreword / by Paolo Cherchi Usai -- Introduction -- The colors of modernity -- Hand coloring and the intermediality of the cinema -- Transformation and uplift: stenciling, tinting, and toning -- Color cinema, from gentility to abstraction -- Conclusion.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
JSTOR
Keywords: Color cinematography -- History; Colorization of motion pictures -- History; Silent films -- History and criticism; Colors in motion pictures; Cinéma en couleurs -- Histoire; Colorisation des films -- Histoire; Films muets -- Histoire et critique; Couleurs au cinéma.; ART -- Film & Video; PHOTOGRAPHY -- Techniques -- Cinematography & Videography; PERFORMING ARTS -- Film & Video -- History & Criticism; Color cinematography; Colorization of motion pictures; Colors in motion pictures; Silent films; Criticism, interpretation, etc; History